Evaluating the environmental impact of selected chemical de-icers. Issue 3 (22nd February 2020) - Li, Xiang; Van Aken, Benoit; Mckenzie, Erica; Zhang, Huichun; Abboud, Bechara; Davenport, William
Abstract: In this study, the environmental impacts of six commercial chloride-based de-icer products, including Rock Salt and Salt Brine, were evaluated. The nutrients, oxygen demand, heavy metal concentration, corrosion and toxicity of all six de-icers were analysed. With an assumed 500-fold dilution, the test results were compared to the public water-quality criteria. The results show that the selected chemical de-icers have little chance of severely damaging the environment and ecosystem under a normal dilution scenario. However, attention needs to be paid to small water bodies and sensitive receiving water.